(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: This study states that, the environment became polluted even after consistent efforts byvarious governments and organizations. Pollution due to various factors was out of control all over the worldand it was badly affecting human lives as well as the mother earth. It was very essential to control thesepollutants because the environmental and health interaction was closed, but it was not possible practically.Lockdown due to Covid 19 has played a very vital role in controlling these pollutants; it has given a muchneeded break to our mother earth.The outbreak of Covid -19 viruses started in Wuhan, China in the month of December 2019. After itsoutbreak, it’s called as Covid-19 worldwide. By March 2020, World health organization declared it as aglobal pandemic disease. This disease has forced complete world at almost a stop these days no humanmovements are allowed unless and until it is really needed or is an emergency situation, the governmenthas taken very strict steps to control the spread of this disease all over the world and various countrygovernments have declared lockdown in their respective countries. Everybody is restricted from movingoutside their houses, even all vehicles are restricted, shops and factories are compulsorily restricted fromfunctioning. Closed factories and companies are showing considerable positive effects on health. Otherwisein developing country like India environmental pollution has serious impact on people’s health it was badlyaffecting human respiratory and cardiac system and due to which peoples were losing their lives. Waterpollution was affecting human digestive system, renal system. But now due to controlled global warmingcommunicable diseases are reduced. Ban on vehicles reduced traffic pollution, reduced accident rates too.Peoples are at rest at their houses, they are showing many positive behavioral changes as they are spendingquality time with family, they are engaged in cleaning their home regularly. Due to this lockdown unlikehuman being’s nature too got its much needed break after many centuries. Conclusion: Aim of this studyis to compare the situation of pollution and other related factors before and after lockdown along withits comparison and to identify unseen positive effects of the Covid-19 lockdown which we have neverseen before . If all these positive effects continued for a long time, then it will definitely become beneficialfor the living creatures as well as to mother earth.